Criss-cross heart: report of two cases, anatomic and surgical description and literature review - Oliveira,Ítalo Martins de (2013)
Criss-cross heart is an extremely rare anomaly, characterized by an abnormal rotation of the ventricular mass along its major axis. It may be associated with any malformation of the heart segments and connections. Due to the complex structural changes and rarity of the anomaly, the rotation of ventricular axis is often misdiagnosed. In this paper, two cases of criss-cross heart are reported, with emphasis on diagnostic and surgical techniques used to corrected the main defects. A literature review on the subject is also presented which, although sparse, emphasized on the morphologic, diagnostic and surgical aspects of the anomaly.